THE STRATEGY OF STUDENTS ENTREPRENEURING THROUGH RELIGIUS CULTURAL PROGRAMS - Nurdiana, Wahyu (Atthulab: Islamic Religion Teaching and Learning Journal, 2019)
This study aims to: 1) Know the strategy of moral coaching students in SMPN 3 Cikupa and SMP Al-Fattah Tigaraksa Tangerang. 2) To know the implementation of the moral guidance strategy of students through religious culture program at SMPN 3 Cikupa and SMP Al-Fattah Tigaraksa Tangerang. 3) Knowing what the supporting and inhibiting factors in the implementation of moral strategy of students through religious culture program in SMPN 3 Cikupa and SMP Al-Fattah Tigaraksa Tangerang. 4) Knowing the results of the implementation of moral coaching strategies through religious cultural programs to moral coaching students at SMPN 3 Cikupa and SMP Al-Fattah Tigaraksa Tangerang. The method used in this research is descriptive-qualitative with the form of field research approach (field research) or case study (case study). The data used are qualitative data. The data sources used consist of primary data sources and secondary data sources. The data collection is done by observation, interview, documentation and bibliography.